Faculty Participation in University Governance and the Effects on University Performance - William O. Brown Jr. (Claremont McKenna College, Department of Economics, 1999)
This paper examines the relationship between faculty participation in university decision making and university performance. Using an aggregated measure of faculty participation, McCormick and Meiners (1988) find that increased faculty control in decision making is associated with lower levels of institutional performance. Building on the existing university governance literature, this paper argues that the optimal level of faculty participation varies by decision type. Disaggregating the data by faculty participation into different decision types produces results that are consistent with this hypothesis. Increased faculty participation may be good or bad; the effects vary by the type of decisions in which faculty participate.
Keywords: G3; I2; L3; 330; higher education; organizational governance